Interrelation between systemic inflammation markers, endothelial dysfunction and coronary heart disease clinical course after community-acquired pneumonia - N. S. Mykhailovska; T. O. Kulynych (Zaporozhye State Medical University, 2015)
Extensive research has established that community acquired pneumonia has negative impact on clinical course on coronary heart disease (CHD), but the pathogenic mechanism was not understood. Aim. To study the pro-inflammatory biomarkers and endothelial dysfunction, its interrelation with CHD clinical course in patients with community acquired pneumonia, 90 patients were recruited. Methods and results. The I (main) subcohort included 60 CHD patients with community acquired pneumonia, the II subcohort included 30 stable angina pectoris without community acquired pneumonia and 21 community acquired pneumonia patients, ІІІ clinical group - without CHD. Using immunoassay high-sensitive C-reactive protein, neopterine and pregnancy-associated protein A were assessed. Among patients with CHD and community acquired pneumonia the significant increasing of all biomarkers was observed at the beginning and after 1 month of disease. The increasing of these biomarkers was associated with was associated with poorer prognosis in CHD patients during 1 year follow-up. Conclusions. The direct correlation between high-sensitive C-reactive protein and neopterine, РАРР-А was found, which suggests the pathogenic ties between immune inflammation and endothelial dysfunction among patients with CHD and community acquired pneumonia.